Public Perception of the Millennium Development Goals on Access to Safe Drinking Water in Cross River State, Nigeria - David D. Eni; William M. Ojong (International Journal of Evaluation and Research in Education (IJERE), 2014)
This study evaluated the public perception of Millennium Development Goals (MDGs) of environmental sustainability with focus on the MDG target which has do with reducing the proportion of people without access to safe drinking water in Cross River State, Nigeria. The stratified and systematic sampling techniques were adopted for the study, considering a study population of 2,892,988 with a sample size of 1260 respondents. The data was analysed using t-test analysis for single mean at .05 levels of significance. The result obtained from the Cronbach Alpha reliability of the instrument was .67, while the mean ( ) and standard deviation were 20.98 and 3.73 respectively. The instrument measure what it was designed to measure in the study. The result showed a significant but positive t-value of 12.21. The calculated t-test of 12.2 was found to be significantly greater than the critical t-value obtained in the result; it implies that respondents have adequate perception of MDGs of environmental sustainability in terms of access to safe drinking water. The perception of MDGs of environmental sustainability was significantly high. It was recommended that environmental sustainability issues should be given priority and included in the school curriculum at all levels of education system. Secondly, the Cross River Government should embark on water schemes across the State to provide portable and affordable water in the State as it has done in Calabar Metropolis thereby meeting the MDG target, to halve, by 2015, the proportion of people without sustainable access to safe drinking water.DOI: http://dx.doi.org/10.11591/ijere.v3i4.6655